PENGARUH MOTIVASI, KOMPENSASI DAN LINGKUNGAN KERJA, TERHADAP KINERJA KARYAWAN: (STUDI KASUS PT INFIMEDIA SOLUSI PRATAMA) - Nurlaela Eva Puji Lestari (Universitas Bina Sarana Informatika, 2017)
The purpose of this research is to know the effect of motivation, compensation and working area toward employee’s performance (case study at PT Infimedia Solusi Pratama). The instrument of this analysis is double regression analysis. The population of this analysis is all employees at PT. Infimedia Solusi Pratama and it has 43 people as sample. Analysis model which is used is descriptive model with SPSS V.17. this research using taking sampling technique (total sampling technique or census). Instrument of this research is questioner for about 100 questions. The result of this research shows : 1) there is effect between internal communications towards employee’s performance, 2) there is effect between compensation towards employee’s performance, 3) there is effect between working area towards employee’s performance, 4) there is effect among internal communication, compensation, and working area simultaneously toward employee’s performance, 5) koefisien determination or (R2) is 0,695 or 69,5%. It means that effect of internal communications, compensation, and working area toward employee’s performance simultaneously is 69,5% and for the rest is 30,5% influenced by other factor. Based on the research which has been done, it can be seen that there is effect simultaneously among motivation (X1), compensation (X2), and working area (X3) toward employee’s performance. (Y).